From the History of Religions in Asia to a Global History of Religion - Christoph Kleine (AЯGOS)
This article examines the relationship between two contemporary perspectives on conceptualizing a global history of religion. The first is anchored in an entangled conceptual history, reconstructing the genealogy of “religion” back to the colonial nineteenth century. The second favours a multicentred perspective in studying knowledge systems and general concepts independent of the West and predating global modernity. By analysing Japanese religious history, the article illustrates both the potential for and the necessity of integrating these two approaches.